Phytotherapy for the Treatment of Glioblastoma: A Review - Mian, Shan Yasin; Nambiar, Abhishek; Kaliaperumal, Chandrasekaran (Frontiers in Surgery, 2022)
Background Phytotherapy; the study of extracts of natural origin in the treatment of disease, has scarcely been applied in the management of GBM. A body of literature exists studying in-vitro, the use of natural extracts against GBM cells. Given persisting poor prognoses, we evaluated, through systematic literature-review the therapeutic potential of naturally sourced extracts in-vivo. Methods Using OVID, MEDLINE and EMBASE databases were searched with compound search term. Abstracts and full-texts were double-screened by independent reviewers. Results Nine hundred and eighty-seven articles, excluding duplicated were screened, leading to the inclusion of 14. Amongst murine studies, Ashwagandha, Coptis Chinensis and Fructus Ligustri Lucidi in unprocessed forms, produced significant reductions in tumour volume. Amongst human studies, Perrilyl alcohol, derived from Lavender, reduced angiogenic cytokines in 31% of subjects, halted 6 month disease progression in 48.2% of subjects, and improved mean survival by 4.9 months in separate studies, respectively. Conclusion Although cursory, current trends in literature demonstrate the value of inhaled Lavender extract in the treatment of GBM, offering tangible clinical benefit to patients receiving conventional treatments. Furthermore, the administration of 8, discrete extracts in mice to produce significant responses in survival and tumour volume, suggest there is further scope for study. Although additional safety tests are required, currently, phytotherapeutics are the crossover to clinical translation, and additional trials are warranted to expound upon thus far promising results.